Pengaruh Motivasi Kerja, Komunikasi Internal, dan Manajemen Waktu terhadap Kinerja Karyawan : (Studi Kasus di Hotel Liberta Hub Blok M) - Hilal Haekal; Syaiful Anwar (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study was conducted with the main objective of determining and analyzing the influence of work motivation, internal communication, and time management on employee performance, with a population of 30 employees at the Liberta Hub Hotel Blok M. The data collection technique used a Likert-sized questionnaire designed to explore respondents' perceptions regarding the variables studied. Furthermore, the data obtained was processed using Microsoft Excel 2018 and SPSS version 25 software to make the analysis results more measurable and accurate. The analytical method used was multiple linear regression, which was chosen because it was able to show the magnitude of the influence of each independent variable on the dependent variable, namely employee performance. The results revealed that work motivation has a significant influence, where the higher the motivation of employees, the higher their performance. Internal communication also has a positive effect because the flow of clear, open, and effective information can support work coordination, reduce misunderstandings, and strengthen synergy within the team. In addition, time management has been shown to provide an important contribution, because the ability to manage work time well encourages efficiency, timely task completion, and optimal target achievement. Overall, this study confirms that work motivation, internal communication, and time management are factors that cannot be ignored in efforts to improve employee performance. The practical implications of this research result are expected to serve as a basis for the management of Hotel Liberta Hub Blok M to develop a more focused human resource development strategy, so that employee productivity continues to increase while supporting the provision of high-quality service to customers.